FAKTOR YANG MEMENGARUHI PERILAKU KONSUMEN TERHADAP PERMINTAAN CABAI MERAH KERITING DI PASAR KRANGGAN YOGYAKARTA - Untoro Hariadi; Rini Anggraeni; Boby Prayoga (Fakultas Pertanian, Universitas Janabadra, 2024)
Yogyakarta's Kranggan Market is a traditional market with many vegetable traders selling large red chilies. The problem in the field is that many people consume large red chilies as the main ingredient in every dish. This research aims to determine consumer behavior regarding the demand for curly red chilies and the factors influencing the demand for curly red chilies at the Kranggan Market in Yogyakarta. The sampling method was carried out directly by interviewing 30 red chili consumers using a questionnaire. The data analysis method is a multiple linear equation model with the Ordinary Least Square (OLS) estimation method used in this research. The research results showed that the majority of respondents, namely 66%, agreed that red chili was the most sought-after spice when shopping. As many as 20% of consumers agreed that only one type/variety of red chili was purchased at traditional markets. Factors that influence consumer behavior in consuming red chilies are price and income. The results of the coefficient of determination test (R2) showed that 75.3% of the influence of the variables age, price, income, and number of family dependents on demand for curly red chilies could be explained by the independent variables used in the research.